2013
DOI: 10.1186/1471-2202-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cortical plasticity and improved motor performance following unilateral and bilateral transcranial direct current stimulation of the primary motor cortex

Abstract: BackgroundTranscranial direct current stimulation (tDCS) is a non-invasive technique that modulates the excitability of neurons within the primary motor cortex (M1). Research shows that anodal-tDCS applied over the non-dominant M1 (i.e. unilateral stimulation) improves motor function of the non-dominant hand. Similarly, previous studies also show that applying cathodal tDCS over the dominant M1 improves motor function of the non-dominant hand, presumably by reducing interhemispheric inhibition. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 60 publications
(114 reference statements)
4
63
2
Order By: Relevance
“…Online training-induced improvements in non-dominant hand dexterity on the Purdue Pegboard and Jebsen-Taylor tests can be facilitated by anodal tDCS (Bastani & Jaberzadeh, 2014;Convento, Bolognini, Fusaro, Lollo, & Vallar, 2014;Kidgell, Goodwill, Frazer, & Daly, 2013). Kidgell and colleagues (2013) found that anodal tDCS applied to non-dominant M1 using a unilateral (cathode over contralateral orbit) or bilateral (cathode over contralateral M1) montage resulted in similar improvements of dexterity function (assessed with the Purdue Pegboard Test) in the non-dominant hand compared with sham stimulation .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
“…Online training-induced improvements in non-dominant hand dexterity on the Purdue Pegboard and Jebsen-Taylor tests can be facilitated by anodal tDCS (Bastani & Jaberzadeh, 2014;Convento, Bolognini, Fusaro, Lollo, & Vallar, 2014;Kidgell, Goodwill, Frazer, & Daly, 2013). Kidgell and colleagues (2013) found that anodal tDCS applied to non-dominant M1 using a unilateral (cathode over contralateral orbit) or bilateral (cathode over contralateral M1) montage resulted in similar improvements of dexterity function (assessed with the Purdue Pegboard Test) in the non-dominant hand compared with sham stimulation .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
“…This is consistent with the findings of Hummel et al (2005) that JTT improvements persisted for at least 25 minutes after anodal tDCS. Changes in cortical excitability and intracortical inhibition have also been shown to persist after the stimulation is turned off (Ardolino et al , 2005, Stagg et al , 2009, Di Lazzaro et al , 2012, Bastani et al , 2013b, a, Kidgell et al , 2013, Kim et al , 2014, Moliadze et al , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Standardization of application across different laboratories and full transparency of stimulation procedures provides the basis for comparability of data which supports reliable interpretation of results and evaluation of the proposed mechanisms of action. Transcranial direct current stimulation (tDCS) or transcranial alternating current stimulation (tACS) differ by parameters of the applied electrical current: tDCS consists of an unidirectional constant current flow between two electrodes (anode and cathode) [2][3][4][5][6] while tACS uses an alternating current applied at a specific frequency 7 . Transcranial random noise stimulation (tRNS) is a special form of tACS that uses an alternating current applied at random frequencies (e.g., 100-640 Hz) resulting in quickly varying stimulation intensities and removing polarity-related effects 4,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…NEBS applied to the primary motor cortex (M1) has attracted increasing interest as safe and effective method to modulate human motor function 1 . Neurophysiological effects and behavioral outcome may depend on the stimulation strategy (e.g., tDCS polarity or tRNS), electrode size and montage [4][5][6]14,15 . Aside from subject-inherent anatomical and physiological factors the electrode montage significantly influences electric field distribution and may result in different patterns of current spreading within the cortex ; 2) anodal tDCS as bilateral M1 stimulation (also referred to as "bihemispheric" or "dual" stimulation) with the anode positioned on the M1 of interest and the cathode positioned on the contralateral M1 5,6,14,23,24 ; the basic idea of this approach is maximizing stimulation benefits by upregulation of excitability in the M1 of interest while downregulating excitability in the opposite M1 (i.e., modulation of interhemispheric inhibition between the two M1s); 3) For tRNS, only the above mentioned unilateral M1 stimulation montage has been investigated 4,6 ; with this montage excitability enhancing effects of tRNS have been found for the frequency spectrum of 100-640 Hz 4 .…”
Section: Introductionmentioning
confidence: 99%